Investment Feasibility of Ecotourism Development in Small Island - Agus Romadhon; Suhartono Suhartono; Dyah Ayu Sulistyo Rini (Journal Omni-Akuatika, 2020)
The small islands have unique natural conditions, although they are surrounded and isolated by the sea, their natural environment is well preserved and offers interest views. Ecotourism is one of the activities to utilize ecosystem services of small islands. The study aimed to evaluate the suitability of tourism and assess the feasibility of investing in ecotourism development using the Tourism Suitability Index (TSI) and the Small Island Investment Index (SII). The research location is on Saor Island, one of the small islands in Madura Island. The results showed that Saobi Island is suitable for diving and snorkelling tourism (2.0 ≤ TSI <2.5). Infrastructure conditions, governance, socio-culture make Saobi Island a suitability investment place for tourism investment (SII = 3.70). Saobi Island policies to support small island ecotourism investments are improving the quality of accessibility, land ownership, availability of infrastructure, reinventing local traditions and improved the quality of human resources Keywords: ecotourism, Saor island, small island investment